2022
DOI: 10.1063/5.0086906
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation, chaos, multistability, and organized structures in a predator–prey model with vigilance

Abstract: There is not a single species that does not strive for survival. Every species has crafted specialized techniques to avoid possible dangers that mostly come from the side of their predators. Survival instincts in nature led prey populations to develop many anti-predator strategies. Vigilance is a well-observed effective antipredator strategy that influences predator–prey dynamics significantly. We consider a simple discrete-time predator-prey model assuming that vigilance affects the predation rate and the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Numerous researchers [17,18] have found that population models with two species cannot correctly reflect reality, and only models with three or more species can represent a large number of important behaviors. The development of mathematics also illustrate that threespecies food chain models are much more complex features than two-species models [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researchers [17,18] have found that population models with two species cannot correctly reflect reality, and only models with three or more species can represent a large number of important behaviors. The development of mathematics also illustrate that threespecies food chain models are much more complex features than two-species models [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Examples include ecosystems and chemical reactions [19][20][21]. More signifcantly, discrete-time models are comparably simpler and less computationally intensive [22]. Because of this, compared to continuous forms, discrete-time model formulation and simulation are typically more straightforward, practical, and accurate.…”
Section: Introductionmentioning
confidence: 99%
“…Most discrete-time epidemic models not only are simple analogies of continuous epidemic models, but also show complex dynamic behaviors that the corresponding continuous models cannot show. The discrete-time model is capable of producing extremely complicated dynamics, even in a one-dimensional instance [14]. Many interesting and important research works can be found in [15][16][17][18][19] and the references cited therein.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have explored the use of computers to model the dynamics within the local parameter variation. Therefore, the numerical methods are helpful not only to validate our analytical results but also to better demonstrate and understand the dynamics of the model [14]. In this paper, we analyze a discrete-time model with the help of various numerical tools and techniques.…”
Section: Introductionmentioning
confidence: 99%